CONSTITUTIONAL REVOLUTION IN IRAN - Yulduz U. Akramova (International Journal Of History And Political Sciences, 2023)
The article reveals the essence of the constitutional revolution, which left a huge mark in the history of the Iranian state and lasted for a long time. The mistakes of the Qajar dynasty in domestic and foreign policy; the irreparable blow of foreign countries and capitals to Iran's economy; not only in the economic sphere, but also in management issues, there is talk of increasing dependence on foreign countries. Despite the fact that it was the first revolution in the history of Iran, it was a revolution that spread to a wide area and caused great changes in the life of the state administration. The reasons, results, achievements and shortcomings of this revolution, which achieved great positive growth and changes in the history of Iran during the years 1905-1911, are discussed below.